Exploring Public Perceptions of ChatGPT in Education through Netnography and Social Media Analysis - Listyanto Aji Nugroho; Emy Wuryani (Gagasan Pendidikan Indonesia, 2023)
This study aimed to examines public perceptions of ChatGPT, a language model developed by OpenAI, particularly in the context of education. Netnography and Social Network Analysis were employed in this study. Using Instagram as the main source of data, the top 10 posts related to ChatGPT were analyzed, and three active groups discussing the technology were identified: university accounts, education influencers, and AI technology developers. A keyword analysis was conducted, and 24 related search terms were grouped into four clusters, showing that ChatGPT is directly related to artificial intelligence, machine learning, learning systems, research, data mining, ethics, and authorship. Overall, the development of ChatGPT has attracted the attention of various parties, particularly in the field of education. There is significant concern about the impact of this technology on humanistic values in education, but many parties are also striving to optimize ChatGPT's potential to improve effectiveness and efficiency in the teaching and learning process. Therefore, a better understanding and adaptation of ChatGPT technology is needed to minimize negative impacts and maximize its positive potential in the world of education.